Contributions of Public Primary School Teachers Socio-Demographic Variables to Child Abuse Reporting Practices in Nigeria - Adamu, Chidubem Deborah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
The study analyzed the contributions of public primary school teachers’ socio-demographic variables to child abuse reporting practices in Alimosho Local Government Area of Lagos State, Nigeria. These were to examine the contributions of the socio-demographic variables of public primary school teachers to child abuse reporting practices and determine the type of association existing between teachers’ socio-demographic characteristics and child abuse reporting practices in the study area. This research is quantitative and utilizes a cross-sectional research design. The population for the study was all the 1,105 public primary school teachers in Alimosho, Local Government Area of Lagos State, Nigeria. The study sample consisted of 314 public primary school teachers in the study area, using a multi-stage sampling technique in four stages. Data collection techniques using questionnaires. The data collected was analyzed using descriptive and inferential statistical analysis. Results showed that the mean age of respondents was 35.89 ± 7.95 years; 72(24.8%) of the respondents were primary five teachers; males were 51.7%; 50% of the respondents were Christians; 49.7% of the respondents had 5-9 years of teaching experience. Also, results showed that religion (X2 = 0.47, p = 0.007), years of teaching experience (X2 = 13.38; p = 0.001), and level of qualification (X2 = 11.21, p = 0.02) varied significantly with respondents’ child reporting practices while respondents age (X2 = 6.99, p = 0.13), gender (X2 = 0.001, p = 0.97), and primary school teachers’ class (X2 = 15.59, p = 0.79) were not significant to child abuse reporting practices.